Accounting Analysis of Sharia Based Financing in the Selin Karya Murni MSME (Descriptive Qualitative Study) - Soemaryono; Rudi Pratono (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This research aims to understand the meaning of accounting for installment sales financing under the sharia system in micro, small, and medium enterprises (MSMEs) at Selin Karya Murni. Using a qualitative approach with an ethnomethodological framework, through analysis of indexicality, reflexivity, and shared understanding. This research collects data through interviews, observations, and company documents, then compares it with the Al-Qur'an and Hadith to assess its conformity with sharia principles. The research results show that the implementation of sharia financing at Selin Karya Murni emphasizes contract transparency, no interest, and fairness for both parties, thereby providing convenience for consumers without late fees and aligning with Islamic economic values. This research enriches the discourse on sharia accounting practices at the MSME level, provides practical guidance for business actors who wish to implement sharia-based financing, and theoretically develops Islamic accounting by connecting ethnomethodological findings with Islamic law. The limitation of the research lies in its focus on a single case study of MSMEs, which limits generalizability. It is recommended that further research involve more MSMEs to make the results more representative.